2015
DOI: 10.3892/ijmm.2015.2279
|View full text |Cite
|
Sign up to set email alerts
|

Numb downregulation suppresses cell growth and is associated with a poor prognosis of human hepatocellular carcinoma

Abstract: Numb, an endocytic adaptor, is a known cell fate determinant that participates in asymmetric cell division. The present study aimed to explore the potential roles of Numb in hepatocarcinogenesis. Numb expression was investigated in hepatocellular carcinomas (HCC) with reverse transcription-quantitative polymerase chain reaction and immunohistochemical examination; its association with the prognosis of HCC patients was analyzed. In addition, the effects of Numb deletion on proliferation of HCC cells and its rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Although the present study observed interactions between Numb and the Notch pathway in lung ADC, the contribution of the other pathways to the tumor suppressive role of Numb requires further investigation. Whereas, it has been reported that Numb promotes cell proliferation and cell cycle of hepatocellular carcinoma, inhibiting p21 and modulating CDK4 and SKP2 [ 13 , 35 ]. Numb might interact with cell cycle molecules to promote the growth of lung SCC, although we have not yet investigated this.…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study observed interactions between Numb and the Notch pathway in lung ADC, the contribution of the other pathways to the tumor suppressive role of Numb requires further investigation. Whereas, it has been reported that Numb promotes cell proliferation and cell cycle of hepatocellular carcinoma, inhibiting p21 and modulating CDK4 and SKP2 [ 13 , 35 ]. Numb might interact with cell cycle molecules to promote the growth of lung SCC, although we have not yet investigated this.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of HCC patients is 50–70% ( Xie et al, 2015 ). Currently, liver transplantation is the only effective curative modality.…”
Section: Digestive System Cancersmentioning
confidence: 99%
“…Recently, a growing body of evidence has suggested that Numb may act as a tumor suppressor in various tumor types, including hepatocellular carcinoma, malignant pleural mesothelioma, and breast cancer (16)(17)(18). The downregulation of Numb is associated with a poor prognosis in hepatocellular carcinoma (19), salivary gland carcinoma (20), and esophageal squamous cell carcinoma (21). However, the expression of Numb is greatly heterogeneous among different cells within a tumor mass (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%